Constraints and consequences of implementing Digital Health: Cross-National evidence and implications for Africa - Loonat, Yusuf (My University, 2021)
Introduction: African countries lag the rest of the world in terms of adoption and implementing e-health policies. This in turn severely affects their health outcomes. Objectives: The objectives of this paper where to explain: 1. Africa’s low level of adoption of e-health policies. 2. To what extent does Africa’s low level of adoption of e-health policies translate into inferior health outcomes in specific life expectancy. Methods: Data of 125 countries from the World Health Organization (WHO) were used in regression analysis. Results: Africa’s low level of adoption of e-health policies are as a result of poor economic development and lack of public expenditure in healthcare. Africa’s low level of adoption of e-health policies translate into having inferior health outcomes such as a lower life expectancy of 8 years less than countries from other continents. Conclusion: This study has provided evidence that African countries have lagged in their adoption of e-health policies and even after taking into account their general low levels of economic development and insufficient health expenditure their adoption capacities still are low
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of e-Science, 2021